SAT0227 MYOCARDIAL FIBROSIS IS ASSOCIATED WITH ANCA STATUS, ORGAN INVOLVEMENT AND DISEASE SEVERITY IN PATIENTSWITH GRANULOMATOSIS WITH POLYANGIITIS. (June 2019) - Giollo, Alessandro; Dumitru, Raluca-Bianca; Swoboda, Peter; Plein, Sven; Greenwood, John; Buch, Maya; Andrews, Jacqueline
Abstract : Background: Granulomatosis with polyangiitis (GPA) is a systemic vasculitis with an increased burden of cardiovascular (CV) events compared to the general population, but the prevalence of primary cardiac involvement in this disease is unknown. Objectives: The objective of this prospective study was to describe with cardiac magnetic resonance (CMR) the myocardial abnormalities associated with GPA and their correlations with disease characteristics. Methods: Twenty-six patients with GPA and no prior CV disease (CVD) or diabetes mellitus underwent contrast-enhanced CMR, including late gadolinium-enhancement (LGE), T1 mapping for native T1 and extra-cellular volume (ECV) quantification for assessment of myocardial fibrosis and tissue tagging for assessment of left ventricular (LV) function. Characteristics of disease, treatments and CV risk factors were collected; disease relapse was defined as reappearance or worsening of vasculitis symptoms requiring an increase of the current treatment or introduction of additional immunosuppressive medication. Twenty-five healthy volunteers (HV) with comparable age, sex, BMI and arterial blood pressure served as controls. Results: Patients with GPA (median age 58 years, disease duration 8 years, BVAS 2; females 46%, PR3 ANCA 58%) had similar cardiovascular risk profile to HV. A focal, non-ischemic LGE pattern of fibrosis was detected in 24% of patients and no controls (p=0.010; Table 1 ). Patients with myocardial LGE were more frequently PR3 ANCA negative (93% vs 7%, p=0.007), and they presented more frequently with involvement of the lower respiratory tract (75% vs 25%, p=0.097) and skin (63% vs 38%, p=0.087). Values of LGE-related fibrotic mass were higher in patients presenting with renal involvement (p=0.036). Native T1 and ECV were higher in patients with GPA than HV (Table 1 ); ECV was higher in those with relapsing disease, and native T1 was inversely associated with PR3 ANCA (β=-0.664, p=0.001). Peak systolic strain was slightly reduced in GPA than controls (Table 1 ); LV ejection function (LVEF) was inversely correlated with disease duration (β=-0.454, p=0.026). Conclusion: Patients with GPA had significant myocardial abnormalities on CMR compared to HV. ANCA status, systemic organ involvement and disease severity were associated with CMR markers of myocardial fibrosis. CMR could be a useful tool for identification and future risk stratification of myocardial involvement of GPA. Disclosure of Interests: Alessandro Giollo: None declared, Raluca-Bianca Dumitru: None declared, Peter Swoboda: None declared, Sven Plein : None declared, John Greenwood: None declared, Maya Buch Grant/research support from: Pfizer LTD, UCB, Consultant for: AbbVie, Eli Lilly, EMD Serono, Pfizer Ltd., Sanofi, Jacqueline Andrews: None declared